Accessibility as a determinant of patterns of borrowing and researching of students in selected libraries in U.P. Diliman - De Ocampo, Jayme M. (2004)
Accessibility in terms of the location of the library, is an important factor to consider for the usage of books located in different libraries in U.P. Diliman. Descriptive study was done to evaluate the usage of books with multiple copies found in different unit libraries in U.P. Diliman.